(untitled) (Research, Society and Development, 2021)
Depression and anxiety are diseases that are afflicting more and more young people all over the world. It is at this stage that the highest percentage of risk for suicide is also recorded. As a form of treatment for psychic disorders is used pharmacotherapy, but there are several questions and discussions about the use of psychoactive drugs by young people because of self-medication. This study used a questionnaire and analyzed the number of university students from a private and a public institution in the interior of Bahia, that were diagnosed with depression or anxiety. The results showed a prevalence of young people aged between 24 and 28 years (50%) and revealed that77.7% of the interviewees started using medications after entering higher education. It was also observed that women were the majority of students diagnosed with anxiety or depression. The reason for this may be historical and cultural aspects.